Treatment of Hg(Ⅱ)-tetracycline compound pollution in water by sulfhydryl modified cellulose - LIAN Nengli; LUO Jing; LIN Changxue; WANG Zhiying; ZHUANG Rongjun; XIAO Changye (Gongye shui chuli)
Sulfhydryl modified cellulose(Cell-SH) was used as adsorbent to treat the combined pollution of Hg(Ⅱ) and tetracycline(TC) in aqueous solution. Effects of pH and coexisting cations on the removal efficiency of composite pollution were investigated, and the adsorption isothermal curves, adsorption thermodynamics, and kinetics were discussed. Meanwhile, the adsorption mechanism was explored. The results showed that Cell-SH exhibited good treatment performance on the combined pollution of Hg(Ⅱ) and TC in aqueous solution under pH of 6. The presence of co-existing cations in the solution had a relatively small effect on the removal of Hg (Ⅱ), while the presence of divalent cations had a greater impact on the adsorption of TC. The results of the cyclic regeneration experiments showed that Cell-SH exhibited good cyclic performance in adsorbing TC-Hg (Ⅱ), and after 5 adsorption-desorption cycles, both of the adsorption rate of TC and Hg (Ⅱ) could still maintain above 70%. The adsorption process fitted well with the quasi-second-order kinetic equation and Langmuir isothermal adsorption model, which implied that the adsorption of Hg(Ⅱ) and TC by Cell-SH belonged to monolayer adsorption. The adsorption process was mainly controlled by chemical adsorption. The adsorption of Hg(Ⅱ) and TC by Cell-SH involved electrostatic attraction, complexation, and hydrogen bonding.